2001
DOI: 10.1159/000046554
|View full text |Cite
|
Sign up to set email alerts
|

Activated T-Cell and Bispecific Antibody Immunotherapy for High-Risk Breast Cancer

Abstract: Nontoxic approaches are needed to improve overall survival (OS) and progression-free survival (PFS) for high-risk breast cancer. Combination immunotherapy (IT) consisting of activated T cells (ATC), interleukin-2 (IL-2), and CTL (GM-CSF) was given after peripheral blood stem cell transplant (PBSCT). There were no major toxicities and there appear to be improvements in OS and PFS over historical controls. In order to develop specific cytotoxic T lymphocytes (CTL), we combined ATC with the use of bispecific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Furthermore, we may need to escalate the dose of BSAbxCA125 to overcome the nonspecific binding. Lum et al showed that it is feasible to treat patients with up to 2 Â 10 9 bispecific antibody-treated effector T cells/kg without significant toxicity (38). Thus, it may be safe and efficacious to administer large quantities of bispecific antibody in an effort to improve the efficacy of CIK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we may need to escalate the dose of BSAbxCA125 to overcome the nonspecific binding. Lum et al showed that it is feasible to treat patients with up to 2 Â 10 9 bispecific antibody-treated effector T cells/kg without significant toxicity (38). Thus, it may be safe and efficacious to administer large quantities of bispecific antibody in an effort to improve the efficacy of CIK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies in metastatic breast cancer show some efficacy of this strategy. 36,37 Others have explored using HDC followed by autologous transplantation to first cyto-reduce disease, and then employing allogenic transplantation to optimize GVT effect. 38,39 The concept of inhibiting tumor angiogenesis as a method of cancer treatment and/or prevention was originally proposed over 30 years ago; however, it is not until recently that we have had the development of effective in vivo antiangiogenic strategies allowing for translational medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase III randomized trial is being pursued as a result of this work. Compared with an historic control group, Lum and Sen also observed improved cytokine production, T‐cell activity, and survival in a similar patient group after treatment with IL‐2, GM‐CSF, and activated T‐cells armed with anti‐CD3 × anti‐HER2/ neu bispecific antibody 85…”
Section: Antitumor Activity Of Gm‐csf Therapy Alonementioning
confidence: 92%
“…Compared with an historic control group, Lum and Sen also observed improved cytokine production, T-cell activity, and survival in a similar patient group after treatment with IL-2, GM-CSF, and activated T-cells armed with anti-CD3 ϫ anti-HER2/ neu bispecific antibody. 85 Prostate carcinoma. Evaluation of GM-CSF for the treatment of patients with prostate carcinoma has been assessed by changes in PSA levels.…”
Section: Nonhematologic Malignanciesmentioning
confidence: 99%